2016
DOI: 10.1007/s00125-016-4012-6
|View full text |Cite
|
Sign up to set email alerts
|

Extravascular modified lipoproteins: a role in the propagation of diabetic retinopathy in a mouse model of type 1 diabetes

Abstract: Aims/hypothesisWe aimed to determine whether plasma lipoproteins, after leakage into the retina and modification by glycation and oxidation, contribute to the development of diabetic retinopathy in a mouse model of type 1 diabetes.MethodsTo simulate permeation of plasma lipoproteins into retinal tissues, streptozotocin-induced mouse models of diabetes and non-diabetic mice were challenged with intravitreal injection of human ‘highly-oxidised glycated’ low-density lipoprotein (HOG-LDL), native- (N-) LDL, or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…In an atheromatous plaque, the oxLDL concentration is much higher than in plasma and is associated with plaque instability [ 221 ]. It is similar in the diabetic retina [ 222 ]. However, there is a significant difference between the accumulation of modified lipoproteins in the arteries and the retina.…”
Section: The Role Of Cd36 In Diabetic Complicationsmentioning
confidence: 99%
“…In an atheromatous plaque, the oxLDL concentration is much higher than in plasma and is associated with plaque instability [ 221 ]. It is similar in the diabetic retina [ 222 ]. However, there is a significant difference between the accumulation of modified lipoproteins in the arteries and the retina.…”
Section: The Role Of Cd36 In Diabetic Complicationsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Recently, Yu's group reported that diabetes confers susceptibility to retinal injury imposed by intravitreal injection of modified LDL. 15 These findings suggest that extravasated, modified plasma lipoproteins contribute to the propagation of DR.…”
mentioning
confidence: 90%
“…8 We have also shown that modified LDL is injurious to several retinal cell types, including RPEs. [9][10][11][12][13][14] We therefore hypothesized that extravasated, modified LDL might play an important role in DR development, 15 and might act, in part, by injuring not only the inner BRB but also the outer BRB. We also hypothesized that the protective effects of fenofibrate in DR include preservation of outer BRB integrity and reduction of vascular endothelial growth factor (VEGF) and inflammatory mediator expression.…”
Section: Introductionmentioning
confidence: 99%